2019
DOI: 10.3390/foods8090400
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Profile and Bioactive Properties of Insect Powders Used in Food and Feed Formulations

Abstract: Microbiological, nutritional and bioactive properties of edible powders obtained from Acheta domesticus (house cricket) and Tenebrio molitor (mealworm) were investigated. Except for the enterobacteria, viable bacteria were at a higher concentration in mealworm flour. The diversity evaluation carried out using MiSeq Illumina that mainly identified Citrobacter and Enterobacteriaceae in mealworm powder and members of the Porphyromonadaceae family in house cricket powder. Enterococci were identified and characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 67 publications
5
42
1
1
Order By: Relevance
“…In the first part of the work, a bacterial characterization of cricket powder was carried out through a next generation sequencing (NGS) analysis that allowed for an in-depth evaluation of the occurring bacteria. In accordance with the findings of other authors [ 14 , 20 , 21 ], the taxonomic analysis revealed the presence of three dominant phyla: Bacteroidetes, Firmicutes, and Proteobacteria. Bacteroidetes includes species associated with the gut microbiota of human and insects [ 34 , 35 ] that were probably transferred from intestinal tracts when the crickets were crushed into powder.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the first part of the work, a bacterial characterization of cricket powder was carried out through a next generation sequencing (NGS) analysis that allowed for an in-depth evaluation of the occurring bacteria. In accordance with the findings of other authors [ 14 , 20 , 21 ], the taxonomic analysis revealed the presence of three dominant phyla: Bacteroidetes, Firmicutes, and Proteobacteria. Bacteroidetes includes species associated with the gut microbiota of human and insects [ 34 , 35 ] that were probably transferred from intestinal tracts when the crickets were crushed into powder.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, lactic acid bacteria (LAB) are considered the main group responsible for these improved characteristics, thanks to their activities in the raw matrix and to their different metabolic capabilities [ 18 , 19 ], e.g., peptidase activities, acidification, exopolysaccharides production, and anti-nutritional compound reduction. The LAB of various genera have already been identified in cricket powder formulations [ 14 , 20 , 21 ] through culture-dependent and independent methods. Particularly, together with bacteria associated with the insect gut such as Bacteroides and Parabacteroides spp., the LAB of the genera Enterococcus spp., Lactococcus spp, Lactobacillus spp., and Pedioccoccus have been found.…”
Section: Introductionmentioning
confidence: 99%
“…The microbiological and bioactive properties of powders made from Acheta domesticus and Tenebrio molitor were examined by Concetta Maria Messina and co-workers [ 39 ], who found a higher number of viable bacteria, mainly Citrobacter and Enterobacteriaceae, in mealworm flour than in cricket powder, which, on the other hand, contained more Porphyromonadaceae. The protein hydrolysates of both powders were rich in antioxidants.…”
Section: Resultsmentioning
confidence: 99%
“…The simplicity of the processing outlined in this paper, from washing to blanching, then oven-drying, and blending to powder, exemplifies their ease for inclusions and more frequent use as a food ingredient or dietary supplement. Therefore, this paper also aims to strengthen advocacy for the use of such minimally processed insect powders as processed food ingredients that could affordably be incorporated into other food products [ 34 , 35 , 36 ]. The current literature suggests evidence to support that oven-dried insects are comparable to freeze-dried ones.…”
Section: Discussionmentioning
confidence: 99%